RERAS—robotic colorectal resections and ERAS® in older adults: optimizing recovery or adding complexity? - El-Ahmar, M.; Hardt, J.; Reissfelder, C.; Ritz, J.-P.; Peters, F.; Seyfried, S. (Frontiers in Surgery, 2025)
PurposeRobot-assisted surgery (RAS) has established itself as a minimally invasive approach in colorectal surgery, although evidence on its integration with Enhanced Recovery After Surgery (ERAS®) protocols in older patients remains limited. This study aims to describe short-term outcomes of RAS combined with a perioperative treatment according to the ERAS® protocols in patients ≥70 years.MethodsThis retrospective analysis of a prospectively maintained database includes all patients aged ≥70 years who underwent robotic colorectal resections at two German colorectal cancer centers between January 2019 and April 2024, managed perioperatively according to the ERAS® protocols. Primary endpoints were the patients' short-term perioperative outcomes, including duration of surgery, conversion rate, postoperative Intermediate-Care-Unit (IMC) admission, postoperative complications according to Clavien-Dindo, anastomotic leak and reoperation rate, length of hospital stay, and compliance to ERAS® guidelines. Results are presented descriptively without a comparator arm.ResultsA total of 161 patients (99 colon resections and 62 rectal resections) were included over the study period. Median duration of surgery was 153 (IQR: 130–197) minutes for colon and 243 (IQR: 120–467) minutes for rectal resections. Conversion rates were 1% and 4.8% respectively. Postoperative IMC admission was required in 9.1% (9 Patients) after colon and 12.9% (8 Patients) after rectal-resections, based on individual clinical assesement. Anastomotic leaks occurred in 7 cases (7%) following colon resections, with a total reoperation rate of 10%. Among rectal resections, the anastomotic leakage rate was 9.7% (6 cases) with a total reoperation rate of 16.1%. ERAS® compliance was 91.3% for colon- and 85% for rectal resections. Within the rectal cohort, postoperative complications were associated with a substantially lower perioperative ERAS® compliance compared to patients without complications (73.3% vs. 90.7%). Hospital stay was 5 days (IQR: 4–6 days) for colon- and 6 days (IQR: 5–11 days) for rectal resections. The 30-day readmission rate was 4% (4 cases) for colon and 8% (5 cases) for rectal resections.ConclusionThe integration of RAS colorectal surgery within ERAS® protocols appears feasible and is associated with acceptable short-term outcomes in elderly and comorbid patients. Nonetheless, these results should be interpreted as descriptive observations rather than inferential evidence.